Law Enforcement against Cardsharing Perpetrators in Distributing Smartcard Private Keys on Television Services - Aribowo, Wahyu Wasono Dyan; Purwoleksono, Didik Endro; Suheryadi, Bambang (Law Development Journal, 2024)
The cybercrime has become popular case of which is serious enough for public and the law enforcers do not aside from badness happened at broadcasting service of satellite telecast subscribes to. Till now still require much business which is permanent ossified to finalize the case, this because of more and more and badness modus operandi complex world to be illusory especially by using or through internet as does cardsharing. Equally this term named “an authorized access to computer and service" causing is drawn explains its (the crime characteristic is thought to lay open this badness required expertise and experience of in information technology science. This study aims to know the law enforcement against cardsharing actors in distributing smartcard private keys on television services. The method uses normative research methodology with a qualitative approach. The data used is secondary data based on various reliable and verified sources, including scientific journals, books, online articles, and research reports relevant to the topic under study. Data analysis was carried out in three stages, namely data reduction, data presentation, and conclusion drawing. Based on the research concluded that cardsharing is an illegal activity so that criminal offenses can be imposed under Law No.36 of 199 concerning Telecommunications or even Law Number 19 of 2002 concerning Copyright. After the formation of the ITE Law, which is used as a reference for sanctions imposed on cardsharing offenders on the internet is Article 48 paragraph (2) of the ITE Law and for those who facilitate cardsharing actions, article 50 of the ITE Law applies which regulates criminal sanctions of imprisonment and / or fines with a greater criminal threat.